2013
DOI: 10.1002/mrd.22145
|View full text |Cite
|
Sign up to set email alerts
|

Red wine consumption may affect sperm biology: The effects of different concentrations of the phytoestrogen Myricetin on human male gamete function

Abstract: Myricetin is a natural flavonoid, particularly enriched in red wines, whose occurrence is widespread among plants. Despite extensive research, the beneficial effects of Myricetin on human health are still controversial. Here, we tested the estrogen-like effect of the phytoestrogen Myricetin on human ejaculated sperm biology. To this aim, human normozoospermic samples were exposed to increasing concentrations (10 nM, 100 nM, and 1 µM) of Myricetin. Motility, viability, capacitation-associated biochemical change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 75 publications
0
10
0
2
Order By: Relevance
“…Aquila et al investigated the effects of distinct concentrations of myricetin on human male gamete function. Biochemical changes related to sperm motility, viability, and capacitation, and acrosin activity, as well as glucose utilisation and fatty acid oxidation, were significantly increased with low Myricetin doses; however, higher concentrations are less effective Aquila et al (2013).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Aquila et al investigated the effects of distinct concentrations of myricetin on human male gamete function. Biochemical changes related to sperm motility, viability, and capacitation, and acrosin activity, as well as glucose utilisation and fatty acid oxidation, were significantly increased with low Myricetin doses; however, higher concentrations are less effective Aquila et al (2013).…”
Section: Discussionmentioning
confidence: 98%
“…Myricetin has various biological effects, including anti-inflammatory (Wang et al, 2010), antioxidant (Wang et al, 2017), analgesic, antitumor (Godse et al, 2010;Ma et al, 2015) and antibacterial effects (Silva et al, 2017). Also, a study of ejaculate from fertile men showed that myricetin (10-100 nM) incubation enhanced sperm motility by 25%-50%; similarly, it was noted that 10-100 nM increased viability by 20%-30%, compared to the control (Aquila et al, 2013). These pleiotropic impressions make myricetin an appropriate nominee for the study.…”
Section: Introductionmentioning
confidence: 98%
“…The conversion of NADP+ to NADPH, catalyzed by G6PDH, was measured by the increase in absorbance at 340 nm (Aquila et al, 2013). Spermatozoa samples, washed twice with uncapacitating medium, were incubated in the same medium (control) for 30 min at 37°C and 5% CO 2 .…”
Section: Assay Of the G6pdh Activitymentioning
confidence: 99%
“…Como a miricetina foi relatada por atuar como um agonista para REs em espermatozoides humanos e provocar alterações fisiológicas associadas à capacitação espermática (Aquila et al, 2013), os resultados relatados no presente estudo poderiam ser explicados pelo pressuposto de que a miricetina exerceu seus efeitos no sêmen ovino por meio de um mecanismo envolvendo a sinalização dos REs. Mudanças na cinética espermática também poderiam estar relacionadas à propriedade inibidora da miricetina sobre a atividade ATP-ase das bombas relacionadas ao transporte de íons, tais como o íon Ca 2+ (Thiyagarajah et al, 1991).…”
Section: Arq Bras Med Vet Zootecunclassified
“…O desequilíbrio entre as espécies reativas ao oxigênio (ROS) e os antioxidantes durante a congelação, por exemplo, pode comprometer a fisiologia e a viabilidade das células espermáticas (Apriokur, 2013). A miricetina (3,5,7,3′,4′,5′hexa-hidroxiflavona) é um composto fenólico que apresenta diversos efeitos: antioxidante (Ong e Khoo, 1997) ou próoxidante (Chobot e Hadacek, 2011); efeito fitoestrogênico (Adeoya-Osiguwa et al, 2003;Fraser et al, 2006, Aquila et al, 2013; e efeito inibidor da atividade de ATP-ase das bombas implicadas no transporte iônico (Thiyagarajah et al, 1991).…”
unclassified